ذاتية الشخصيات في رواية حي بن يقظان لابن طفيل - syarifah fahmi (Pascasarjana UIN Raden Mas Said Surakarta, 2024)
With the background described above, several problems can be identified in this study, namely the aspects of psychological analysis of the novel Hayy Bin Yaqzan, the absence of research that discusses the psychology of the characters in the novel, and the essential elements in the novel Hayy Bin Yaqzan. Accordingly, the researcher wants to examine the subjectivity of the characters in the novel Hayy Bin Yaqzan. Written by Ibn Tufayl. The objectives of this research are to describe the subjective form of the characters reflected in the novel Hayy Ibn Yaqzan and explain the essential elements of the novel Hayy Ibn Yaqzan by Ibn Tufayl. In this study, the author is interested in analyzing this novel using Carl Gustav Jung's psychoanalytic theory to analyze the characters' personalities consciously and unconsciously. In this research, the researcher used a type of qualitative descriptive research using literary studies. In the analysis, the researcher uses the interactive analysis model proposed by Miles and Huberman, that is, about reducing data, presenting data, and drawing conclusions. While the data collection method is recording method is used to continue, through recording the data obtained based on the pattern and meaning of sentences. In this novel, the main character Hay bin Yaqzan has an extroverted personality with a kind of senses in consciousness as well as thinkers and tasters who exist in the subconscious. The mother deer personality has an extroverted personality with a taste type in the conscious mind as well as an intuitive and sensitive type in the subconscious. Absal has an introverted personality with a thinking type in consciousness and a taste and intuitive type in the subconscious. Salman has an extroverted personality with an intuitive type in his conscious mind and a tasteful and thinker type in his subconscious